THE PHILOSOPHY OF PANCASILA IN THE RELIGIOUS PERSPECTIVE IN INDONESIA DURING THE COVID-19 PANDEMIC - Yuliana Yuliana (Badan Pembinaan Ideologi Pancasila, 2021)
The philosophy of Pancasila in the religious perspective in Indonesia is associated with social welfare. There are big economic hit and life changes during the COVID-19 pandemic. Therefore, the religious perspective is very crucial to be maintained during this uncertain condition. This paper aims to describe the philosophy of Pancasila in the religious perspective during the COVID-19 pandemic. Method: this is a literature review. The literature was taken from Science Direct and Google Scholar. Inclusion criteria are research and review. Exclusion criteria are short notes and commentary. Finally, there are 15 selected journals. The journals are summarized and narrated. Results revealed that the philosophy of Pancasila in religious perspective is very essential during the COVID-19 pandemic. It is associated with social welfare. The religious perspective must be based on Pancasila and motto of Bhinneka Tunggal Ika to view this nation as a unity. When we view Indonesia as a unity, the religious perspective will be stronger. All of the nations must collaborate to fight against the COVID-19 pandemic. Conclusion: the philosophy of Pancasila in the religious perspective in Indonesia is very essential to ensure the stability of social welfare during the COVID-19 pandemic.